2001
DOI: 10.1590/s0100-29452001000200032
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DA COMPATIBILIDADE DA ENXERTIA EM Prunus sp.

Abstract: RESUMO-A atividade de peroxidase e concentração de fenóis foi determinada com o objetivo de se avaliar aspectos de compatibilidade entre porta-enxertos e enxertos. As amostras foram processadas e obtidas a partir da casca e lenho dos porta-enxertos de pessegueiros (GF 677, Okinawa, Capdeboscq e Aldrighi) e de ameixeiras (Mirabolano e Marianna), enxertados ou não com as cultivares Diamante, Eldorado e Santa Rosa. Concluiu-se que a atividade de peroxidase e a concentração de fenóis foram relacionadas com união e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
11
0
3
Order By: Relevance
“…The symptoms observed in leaves from plants grafted on 'Mirabolano 29C' and 'Marianna 2624' rootstocks are identical to those described by Moreno et al (1993) and Zarrouk et al (2006a), who reported translocated incompatibility in peach and nectarine cultivars grafted on 'Marianna 2624', 'Myrobalan 29C', and other myrobalan clones (P. cerasifera). Graft incompatibility due to increased phenol concentration and peroxidase activity had also been reported in rootstocks 'Mirabolano' and 'Mariana' grafted on peach cultivars 'Diamante' and 'Eldorado' (RODRIGUES et al, 2001). …”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The symptoms observed in leaves from plants grafted on 'Mirabolano 29C' and 'Marianna 2624' rootstocks are identical to those described by Moreno et al (1993) and Zarrouk et al (2006a), who reported translocated incompatibility in peach and nectarine cultivars grafted on 'Marianna 2624', 'Myrobalan 29C', and other myrobalan clones (P. cerasifera). Graft incompatibility due to increased phenol concentration and peroxidase activity had also been reported in rootstocks 'Mirabolano' and 'Mariana' grafted on peach cultivars 'Diamante' and 'Eldorado' (RODRIGUES et al, 2001). …”
Section: Resultsmentioning
confidence: 75%
“…Kester and Hansen (1964) reported that almond cultivars and selections grafted on 'Marianna 2624' exhibited different behaviors, from lack of symptoms up to full incompatibility, six years after field planting, and Grasselly (1983) reported that some 'Myrobalan' clones (P. cerasifera) showed graft compatibility with various peach cultivars. Even though early detection of graft incompatibility has been reported (RODRIGUES et al, 2001;ERREA;BORRUEY, 2004;ZARROUK et al, 2006b;ZARROUK et al, 2010), the methods usually have limitations and evaluation cycles in the field for some rootstock combinations may require several years before any assumptions on compatibility and yield efficiency can be made, especially when genotypes are taxonomically distant (GOLDSCHMIDT, 2014). Thus, graft incompatibility is one of the major hurdles for rootstock improvement and analysis (CIOBOTARI et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Estudos relatados na literatura com diversas espécies de frutíferas e olerí-colas (Rodrigues et al, 2001;Kohatsu et al, 2013) mostram essa relação entre a atividade enzimática e a compatibilidade entre enxerto e portaenxerto, haja vista que quanto mais similar a atividade enzimática entre esses materiais vegetais, menores serão os problemas de incompatibilidade.…”
Section: Abstract Enzymatic Responses On Tomato Graftingunclassified
“…Segundo Oliveira Junior (1999), duas plantas são incompatíveis quando, por motivos intrínsecos a elas, não são capazes de formar uma união completa e equilibrada, impossibilitando o desenvolvimento normal da planta. Esta incompatibilidade surge em vista das diferenças nas características dos crescimentos da copa e do porta-enxerto, diferenças fisiológicas e bioquímicas entre os dois e à produção de alguma substância tóxica de uma parte para a outra, e Rodrigues et al (2001), estudando a compatibilidade da enxertia em Prunus sp, concluíram que a atividade de peroxidase e a elevada concentração de fenóis estão relacionadas com a união incompatível entre enxerto e porta-enxerto. Em experimento realizado em Cordeirópolis, Barbasso et al (2005) observou a ocorrência de linha de goma na região de enxertia para o tangor 'Murcott' sobre o citrumelo 'Swingle' após 10 anos de plantio, mostrando incompatibilidade em plantas formadas com essa combinação.…”
Section: Influência Dos Porta-enxertos Sobre a Qualidade Do Frutounclassified